Advancing Arabic Speaking Proficiency through Pedagogical Innovation with the Isyruna Sualan Language Game Approach - Wahyuni, Sri; Malla, Agussalim Beddu; Martini, Martini (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
This research was motivated by the low level of students’ Arabic speaking ability (maharah al-kalam) at SMA Pest. Putri Yatama Mandiri, which was mainly caused by the lack of innovative teaching methods and minimal active student participation in the classroom. To address this issue, the study aimed to: (1) examine the implementation of the “Isyruna Sualan” language game in Arabic learning, (2) evaluate the outcomes of its application in improving students’ maharah al-kalam, and (3) identify the factors influencing its success in enhancing speaking proficiency. The study employed the Classroom Action Research (CAR) method, conducted in two cycles with class XIA students as the research subjects. Data were collected through pre-tests, post-tests, and observations. Initial findings from the pre-test revealed that only 8 out of 29 students (27.5%) achieved the minimum competency standard in Arabic speaking, while 21 students (72.4%) fell below the requirement. After applying the “Isyruna Sualan” game in the first cycle, 19 students (65.5%) met the standard. The second cycle further improved the results, with 25 out of 28 students (89.2%) successfully achieving the expected level of speaking proficiency. The findings demonstrate that the “Isyruna Sualan” language game effectively enhances students’ maharah al-kalam. Its success was supported by three main factors: the teacher’s role as facilitator, the motivation and enthusiasm of students, and the game’s interactive, goal-oriented design. This research contributes by offering an innovative pedagogical strategy that can be adapted to strengthen Arabic speaking skills in similar educational contexts.